2015
DOI: 10.3390/a8040895
|View full text |Cite
|
Sign up to set email alerts
|

On Some Improved Harmonic Mean Newton-Like Methods for Solving Systems of Nonlinear Equations

Abstract: In this work, we have developed a fourth order Newton-like method based on harmonic mean and its multi-step version for solving system of nonlinear equations. The new fourth order method requires evaluation of one function and two first order Fréchet derivatives for each iteration. The multi-step version requires one more function evaluation for each iteration. The proposed new scheme does not require the evaluation of second or higher order Fréchet derivatives and still reaches fourth order convergence. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Equation (5) is consistency conditions, [34]. The (4) is expressed into coupled equation given in (6) and (7).…”
Section: The Proposed Iterative Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Equation (5) is consistency conditions, [34]. The (4) is expressed into coupled equation given in (6) and (7).…”
Section: The Proposed Iterative Methodsmentioning
confidence: 99%
“…Since 0 X is initial guess, setting 0 X in (7) yields Journal of Applied Mathematics and Physics ( ) 0 0 H X = (16) From (9)and (15),…”
Section: The Proposed Iterative Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We state below a general result which has been proved in Babajee et al [4], showing that α is a point of attraction for a general iteration function…”
Section: Definition 301 (Point Of Attraction)mentioning
confidence: 99%
“…It is straightforward to see that this method requires the evaluation of one function, one first derivative, and one matrix inversion per iteration. Traub [16] suggested that multi-step iterative methods are better way to improve the order of convergence free from second derivatives, such modifications of Newton's method have been proposed in the literature; for example see [1,4,6,11,15] and references therein. The double-step third and fourth order Newton's methods have been proposed in the recent literature, see [9][10][11]15].…”
Section: Introductionmentioning
confidence: 99%